Molecularly controlled epoxy network nanostructures. (13th January 2017) - Morsch, Suzanne; Liu, Yanwen; Greensmith, Polly; Lyon, Stuart B.; Gibbon, Simon R.
Abstract: Epoxy thermosets continue to be used in a variety of coatings, adhesives, and structural composites. Nanostructural heterogeneities have been proposed to determine the physical properties of these materials, but the presence and origin of these features is disputed. Here, we combine nano-chemical imaging and nano-thermal analysis to establish a connection between internal crosslinking and the appearance of nanoscale chemical heterogeneities in epoxy resins. Deflection of an AFM probe is used as a local sensor to detect photothermal expansion in response to infrared excitation, and nanoscale lateral variations are detected in response to illumination at wavenumbers associated with crosslinking. Furthermore, these heterogeneous chemical features correspond to an increased range of local thermal transitions, and only arise within highly cross-linked resins; lightly cross-linked specimens are found to be homogeneous. Graphical abstract: Highlights: The nanostructure of an epoxy resin is controlled using a monofunctional additive. AFM-IR shows that internal nanostructures correspond to chemical heterogeneity. Nano-thermal analysis is used to determine the distribution of local thermal transitions.